Kingella kingae septic arthritis in children: recognising an elusive pathogen. (February 2014) - Williams, Nicole; Cooper, Celia; Cundy, Peter
Purpose: Kingella kingae is an increasingly identified cause of musculoskeletal infections in young children. We report our experience with a recently developed polymerase chain reaction (PCR) method and review the clinical course of children diagnosed with K. kingae septic arthritis in a tertiary referral paediatric hospital. Methods: All positive cases of K. kingae identified by PCR analysis of synovial fluid from August 2010 until July 2013 were included. A chart review was undertaken to determine history, presentation and management. Results: 27 Children (14 male, 13 female) had PCR positive synovial fluid samples for K. kingae with median age of 19 months (range 4 months to 5 years 3 months). The sites of infection were knee (17 cases), hip (2 cases), ankle (5 cases), shoulder (2 cases) and elbow. The median temperature on presentation was 37.1 °C, median peripheral white blood cell count 12.4 (9.9–13.8) × 10 9 /L, erythrocyte sedimentation rate 55 (48–60) mm/h and C-reactive protein 24 (8–47) mg/L. The median synovial fluid white cell count was 21.8 (16.7–45.0) × 10 9 /L. Routine cultures identified K. kingae in only two synovial fluid samples. Two samples were additionally positive for Staphylococcus aureus . Conclusions: Kingella kingae is a significant cause of septic arthritis in young children. The authors recommend maintaining a high index of suspicion in young children presenting with joint inflammation, especially if indices of infection are mild. It appears likely that children historically treated with antibiotics for "culture negative" septic arthritis were infected with K. kingae . PCR techniques for detection of K. kingae should be encouraged.